Assessing small-field output factors using a 2D monolithic diode array on a beam-matched Elekta linear accelerator. (October 2020) - Muñoz, L; Petasecca, M; Metcalfe, P; Bucci, J; Jackson, M; Rosenfeld, A B; Biasi, G
Abstract: The goal of this work was to assess small-field output factors (OPF) on a newly commissioned linear accelerator (linac) using a 'correction-less' 2D monolithic array of diodes, the Duo, which has a spatial resolution of 0.2 mm. The results would validate a set of OPF extracted from the golden beam data (GBD) used to represent the dosimetric characteristics of that linac, an Elekta Versa HD (Elekta, Crawley), fit with an Agility multileaf collimator (MLC). The Duo acquired relative OPF in real time for square fields of nominal side 1, 2, 3 and 4 cm, for 6 MV with flattening filter (WFF) and 6 MV flattening filter free (FFF) photon energies. Results revealed at most a 1.0% difference in OPF when compared to baseline, and bolstered confidence in the acceptance and commissioning of the linac using local GBD as a baseline match.